Chronic tonsillitis and biofilms: a brief overview of treatment modalities - Abu Bakar M (Dove Medical Press, 2018)
Muhamad Abu Bakar,1 Judy McKimm,2 Seraj Zohurul Haque,3 Md Anwarul Azim Majumder,4 Mainul Haque1 1Faculty of Medicine and Defence Health, Universiti Pertahanan Nasional Malaysia (National Defence University of Malaysia), Kuala Lumpur, Malaysia; 2Swansea University School of Medicine, Swansea University, Swansea, Wales, UK; 3University of Dundee, Ninewells Hospital & Medical School, Dundee, UK; 4Faculty of Medical Sciences, The University of the West Indies, Wanstead, Barbados Abstract: Recurrent tonsillitis is described as when an individual suffers from several attacks of tonsillitis per year. Chronic and recurrent tonsillitis both cause repeated occurrences of inflamed tonsils which have a significant impact on a patient’s quality of life. Numerous children suffer from recurrent tonsillitis and sore throats, and these illnesses become part of their life. Antimicrobials can provide temporary relief, but in many cases, tonsillitis recurs. The cause of such recurrent infections have been identified as microorganisms which often create biofilms and a repository of infection in the wet and warm folds of the tonsils. This review discusses different treatment modalities, their advantages and disadvantages, and new treatment options focusing on biofilms. All treatment options should be selected based on evidence and individual need. Keywords: chronic, recurrent tonsillitis, inflammation, tonsillectomy